Normering i klemme mellom språkteknologiske og pedagogiske ordbøker - Fjeld, Ruth Vatvedt (LexicoNordica, 2002)
With the development of dictionaries for language technology lexicography has to cope with a new dictionary typology. Descriptivity or prescriptivity has long been discussed in human-oriented dictionary making. This article tries to point out how language technology evokes a new discussion of this question, on the one side requiring a wider norm, on the other a tighter norm than in dictionaries written for pedagogical situations. This makes the reuse of existing dictionaries as the lexicon part in language technology programs nearly impossible.